Analysis of The Influence of Human Development Index (HDI), Economic Growth and Government Expenditure - Hukom, Maximiliane Leonora Cornelia; Jacobs, Samie Lambert (Journal of Economics Review (JOER), 2024)
Based on the background description presented, the formulation of the problem that is the focus of the research is as follows: do economic growth, human development index, and government spending affect poverty, and do economic growth, human development index, and government spending simultaneously affect poverty in Regencies/Cities in Maluku Province? This study aims to analyze and determine whether economic growth, the human development index, and government spending affect poverty and to analyze and determine whether economic growth, the human development index, and government spending simultaneously affect poverty in regencies/cities in Maluku Province. This study is expected to be a reference for local governments in towns/regencies in Maluku Province to consider making policies related to managing government spending through the quality of economic growth in improving community welfare. It is also a consideration in formulating regional expenditure policies about fiscal decentralization to accelerate development and create a prosperous society free from poverty. The research method used in this study is quantitative research using multiple linear regression analysis techniques with the Ordinary Least Square (OLS) model.